2005
DOI: 10.1177/0013124504271558
|View full text |Cite
|
Sign up to set email alerts
|

School Finance Court Cases and Disparate Racial Impact

Abstract: Although analyses of state school finance systems rarely focus on the distribution of funds to students of different races, the advent of racial discrimination as an issue in school finance court cases may change that situation. In this article, we describe the background, analyses, and results of plaintiffs' testimony regarding racial discrimination in Campaign for Fiscal Equity Inc. v. State of New York. Plaintiffs employed multiple regression and public finance literature to show that New York State's schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…K-12 education finance policies in the United States are ostensibly “colorblind”—school funding is a responsibility of state governments, and none of the funding policies adopted by these governments explicitly considers race. However, for decades researchers have documented racial disparities in school funding (Baker & Green, 2005; Baker et al, 2020; Carey, 2004; EdBuild, 2019; Sosina & Weathers, 2019; Stiefel et al, 2005; Weathers & Sosina, 2019). To explain this pattern, scholars often focus on the way racial and economic segregation between school districts can impact inequities in local education funding (e.g., EdBuild, 2019).…”
Section: Background On Racial Disparities In School Fundingmentioning
confidence: 99%
See 3 more Smart Citations
“…K-12 education finance policies in the United States are ostensibly “colorblind”—school funding is a responsibility of state governments, and none of the funding policies adopted by these governments explicitly considers race. However, for decades researchers have documented racial disparities in school funding (Baker & Green, 2005; Baker et al, 2020; Carey, 2004; EdBuild, 2019; Sosina & Weathers, 2019; Stiefel et al, 2005; Weathers & Sosina, 2019). To explain this pattern, scholars often focus on the way racial and economic segregation between school districts can impact inequities in local education funding (e.g., EdBuild, 2019).…”
Section: Background On Racial Disparities In School Fundingmentioning
confidence: 99%
“…Similarly, researchers have shown that state policies can create or exacerbate existing funding inequities (Alemán, 2007; Baker & Corcoran, 2012). Indeed, a handful of studies have even documented racial disparities in the distribution of state aid that is ostensibly designed to equalize education funding (Baker & Green, 2005; Chellman, 2008; Stiefel et al, 2005). These inequities can be created through what Baker and Green (2005) call “tricks of the trade” (p. 375).…”
Section: Background On Racial Disparities In School Fundingmentioning
confidence: 99%
See 2 more Smart Citations